Sertad1 promotes prostate cancer progression through binding androgen receptor ligand binding domain. Issue 3 (31st October 2018) - Hu, Bingqing; Hu, Haidi; Yin, Mingzhu; Sun, Zhengrong; Chen, Xiaoya; Li, Ying; Sun, Ziyi; Liu, Cong; Li, Ling; Qiu, Yang
Abstract : Androgen receptor (AR) signaling is involved in the initiation and progression of prostate cancer (PCa), which is the most frequently diagnosed nonskin cancer and remains a leading cause of cancer‐related death in men. Further investigation of the involvement of AR signaling in PCa progression is urgently needed. In the present study, we performed a yeast two‐hybrid screen and demonstrated that SERTA domain‐containing protein 1 (Sertad1) is a novel AR‐binding protein that binds to the AR ligand binding domain (LBD). The binding between AR‐LBD and Sertad1 was confirmed by glutathione S‐transferase (GST) pull‐down assays and immunoprecipitation (IP) and confocal immunofluorescence co‐localization experiments. Furthermore, we demonstrated that DHT inhibited Sertad1 protein degradation in prostate cancer cell lines and that Sertad1 knockdown inhibited the proliferation of prostate cancer cells in vitro . In human PCa tumor tissues, Sertad1 expression is positively correlated with AR expression and the Gleason score. Taken together, this report is the first to show that Sertad1 is a novel AR‐LBD‐binding protein, and DHT‐liganded AR‐LBD inhibits Sertad1 degradation. Thus, Sertad1 may represent a novel therapeutic target for the treatment of AR‐positive PCa. Abstract : What's new? Androgen receptor (AR) expression is a major feature of prostate cancer, though the mechanisms underlying its involvement in prostate cancer progression are not fully known. Here, the SERTA domain‐containing protein 1 (Sertad1) was identified as a novel AR ligand‐binding domain (AR‐LBD) protein via cDNA library screening of human male peripheral blood monocytes in a yeast two‐hybrid system. Binding of dihydrotestosterone to AR‐LBD inhibited Sertad1 protein degradation. Furthermore, in human prostate cancer specimens, Sertad1 expression was positively linked to AR expression and Gleason score. The results indicate that Sertad1 may represent a novel therapeutic target for prostate cancer treatment.